Klasifikasi Anak Berpotensi Putus Sekolah dengan Metode Naïve Bayes Di Kabupaten Manokwari - Yoridi, Maria Leonila Yawa; Pakereng, Magdalena A. Ineke (STIKOM Tunas Bangsa Pematangsiantar, 2023)
National development is determined by qualified human resources. Education is a universal activity in the life of a human being. To create quality human beings must be equipped with education, both education at school and outside school. The main problem of education in Manokwari Regency, West Papua is that there are still many children who do not continue their education or stop going to school in the middle of their journey. The Naïve Bayes algorithm with Cross Validation operators was used to analyze the data and predict children who could potentially drop out of school. The results showed that the prediction accuracy rate was 70%. The Naïve Bayes method tends to provide accurate results in predicting children who are not likely to drop out of school with a class precision of 88.89%. However, this method has limitations in predicting children who are potentially or very likely to drop out of school, with class precision and class recall being low for the label of 0.00%.